Reassessing a glacial landscape developed during terminal glaciation of the Late Paleozoic Ice Age in Uruguay - Isbell, John L.; Fedorchuk, Nicholas D.; Rosa, Eduardo L. M.; Goso, César; Alonso-Muruaga, Pablo J. (Sedimentary Geology, 2023)
Whalebacks, roche moutonnées, and S-forms carved on Ediacaran granitoids near Cerro de las Cuentas, Uruguay, along with overlying diamictites, siltstones, and sandstones displaying soft-sediment grooved and striated surfaces in the Pennsylvanian San Gregorio Formation, record the glacial to post-glacial transition in the linked Norte, southern Paraná and Chaco-Paraná basins of Uruguay, Brazil, and Argentina respectively. Early authors reported these features resulted from subglacial abrasion and deposition as lodgement tills and glaciotectonites. Our re-examination reveals a nuanced setting with changing ice thicknesses, subglacial kinematics, and ice proximal glaciomarine dynamics associated with advance and retreat of an ice stream, or multiple advances of the Uruguayan Ice lobe, during glaciation of the Late Paleozoic Ice Age (LPIA) in these basins. The preserved landforms indicate temperate glacial conditions. Whalebacks formed under 1.6 to 2.5 km-thick ice and likely formed when the lobe extended across the Uruguayan and Rio Grande do Sul shields into the adjacent Paraná Basin. Previously unidentified m-scale roches moutonnées cut into one whaleback developed under thinner ice where reduced basal pressure allowed for the opening of air and water-filled cavities, thus facilitating quarrying on the lee side of basement bumps. S-forms provide additional evidence for the occurrence of subglacial waters, indicating that the basal ice was at or above its pressure melting point. The lower meter of the overlying strata consists of interstratified trace fossil-bearing, laminated siltstones; thin-bedded diamictites; and current-rippled sandstones. Trace fossils belonging to the Mermia ichnofacies within the basal siltstones, as well as acritarchs in the overlying siltstones, suggest that these sediments were deposited in ice-proximal subaqueous settings with contributions from meltwater discharge. Graded siltstone laminae suggest settling from suspension likely from meltwater plumes, while thin-bedded diamictites were deposited either as debris flows or as two-component sedimentation with fines settling from suspension and coarser particles introduce as iceberg-rafted dropstones. Current-rippled sandstones indicate the occurrence of underflow currents. Soft-sediment troughs, grooves, and striations cutting these sediments display curved and sinuous paths with some features oriented perpendicular, and one oriented opposite to the overall trend. They contain marginal and terminal berms typical of iceberg scour marks suggesting transit across the area by icebergs calving from a tidewater ice front located to the SE.
Keywords: Iceberg keel marks; Late Paleozoic Ice Age; Roche moutonnées; San Gregorio Fm; Uruguayan Ice Lobe; Whalebacks; dept.esc